The Language of the Weather Forecast in Italian and Spanish Television Broadcasts: Linguistic-Descriptive Analysis of the End of Winter on RTVE and TG5 Television Channels - Vallejo, Rubén González (Lesya Ukrainka Eastern European National University, 2023)
Weather information is of great importance to society due to the impact of the physical environment on everyday life. As a result, popular tradition has disseminated many proverbs related to human activities that have been the subject, over time, of scientific studies, with the aim of verifying the veracity of such predictions. For this reason, this article initially presents a brief bibliographical and regulatory analysis of the evolution of atmospheric language and a presentation of the bodies that regulate its communication in Spain and Italy. Subsequently, a corpus of weather reports extracted during the month of December 2022 from an Italian and Spanish news channel will be illustrated with the aim of studying the communication of weather forecasts from a macro- and microstructural linguistic level, given the lack of studies in both languages in this respect. For this purpose, Speechnotes will be used for the transcriptions and Skecth Engine for the creation of the corpus. As a result of the analysis, Spanish news programmes devote more time to the space of time, show a much higher speed of locution than the Italian corpus, provide a greater number of mechanisms to show probability and uncertainty, and a great variety of linguistic-discursive strategies to exemplify the scientific context. We also find a recurrent gerund, which we will call "atmospheric gerund". In Italian, on the other hand, we find a greater deixis, more synthetic information, and less dynamism in the interaction with the data.
Keywords: atmospheric language; atmospheric forecasting; probability; technicalities; scientific context